Laboratory study on baffled apron as an integral part of an energy dissipator system - Nurfadila, Raaibi (2010)
High water velocity can cause bad Impacts such as erosion, scour, sedimentation and cavitations around spillway toe, weir bed and downstream of river. In order to overcome these problems, the flow velocity has to be reduced. This can be done through constructing an energy dissipating structure at the affected area. Blocks were used in the experimental energy dissipating structure in this study. Various arrangements of blocks at spillway of the model were tested to obtain the most effective result in reducing the water flow velocity. The relation between the percentage of velocity decrease and various block arrangements were determined through the plotted graphs. The decrease in flow velocity varied and depended on the size of blocks, spacing between blocks and the number of rows of blocks. Generally, this study proved that blocks could be used as an energy dissipating structure.